Identifying Clinical Characteristics of Hypoparathyroidism in Turkey: HIPOPARATURK-NET Study - Degertekin, Ceyla Konca; Yavuz, Dilek Gogas; Pekkolay, Zafer; Saygili, Emre; Ugur, Kader; Koca, Arzu Or; Eroglu, Mustafa (Springer, 2022)
Hypoparathyroidism is an orphan disease with ill-defined epidemiology that is subject to geographic variability. We conducted this study to assess the demographics, etiologic distribution, treatment patterns and complication frequency of patients with chronic hypoparathyroidism in Turkey. This is a retrospective, cross-sectional database study, with collaboration of 30 endocrinology centers located in 20 cities across seven geographical regions of Turkey. A total of 830 adults (mean age 49.6 +/- 13.5 years; female 81.2%) with hypoparathyroidism (mean duration 9.7 +/- 9.0 years) were included in the final analysis. Hypoparathyroidism was predominantly surgery-induced (n = 686, 82.6%). The insulting surgeries was carried out mostly due to benign causes in postsurgical group (SG) (n = 504, 73.5%) while patients in nonsurgical group (NSG) was most frequently classified as idiopathic (n = 103, 71.5%). The treatment was highly dependent on calcium salts (n = 771, 92.9%), calcitriol (n = 786, 94.7%) and to a lower extent cholecalciferol use (n = 635, 76.5%) while the rate of parathyroid hormone (n = 2, 0.2%) use was low. Serum calcium levels were most frequently kept in the normal range (sCa 8.5-10.5 mg/dL, n = 383, 46.1%) which might be higher than desired for this patient group. NSG had a lower mean plasma PTH concentration (6.42 +/- 5.53 vs. 9.09 +/- 7.08 ng/l, p < 0.0001), higher daily intake of elementary calcium (2038 +/- 1214 vs. 1846 +/- 1355 mg/day, p = 0.0193) and calcitriol (0.78 +/- 0.39 vs. 0.69 +/- 0.38 mcg/day, p = 0.0057), a higher rate of chronic renal disease (9.7% vs. 3.6%, p = 0.0017), epilepsy (6.3% vs. 1.6%, p = 0.0009), intracranial calcifications (11.8% vs. 7.3%, p < 0.0001) and cataracts (22.2% vs. 13.7%, p = 0.0096) compared to SG. In conclusion, postsurgical hypoparathyroidism is the dominant etiology of hypoparathyroidism in Turkey while the nonsurgical patients have a higher disease burden with greater need for medications and increased risk of complications than the postsurgical patients.
Keywords: Hypoparathyroidism; Hypocalcemia; Epidemiology; Turkey; Parathyroid hormone